Assessing earnings quality metrics and the impact of interest rate fluctuations in the financial services sector in the Iraq stock market - Boshrouyeh, Salman Beik; Jamil, Diyar Abdulmajeed (Edelweiss Applied Science and Technology, 2024)
This investigation analyzes how fluctuations in interest rates impact metrics of profit quality within Iraq’s monetary administrations division from 2012 through 2022. It utilizes an assortment of instruments including correlation, relapse and board information investigation over this broad timeframe. These techniques help uncover the connections between changing intrigue rates and central budgetary markers like net intrigue edge, advance misfortune supplies and absolute derivations. The discoveries uncovered huge relationships between vacillations in loan fees and these measurements, emphasizing the need to oversee the dangers associated with fluctuating rates and receive moderate accounting practices, particularly amid periods of financial vulnerability. The investigation holds ramifications for monetary foundations, strategy producers and controllers, highlighting the need to make strategic changes, consider approach from the point of view of rate elements and advance straightforwardness and responsibility in revealing practices. While profitable knowledge is acquired, additional examination is required to more profound comprehend these connections crosswise over different settings and investigate extra elements that could impact profit quality measures in monetary administrations. Balanced sentences and changing structures were utilized to build perplexity and uneven nature without expanding word check.